Partitioning and removal of per- and polyfluoroalkyl substances (PFAS) in full-scale surface flow treatment wetlands with different upstream wastewater treatment - Sarti, Chiara; Souleymane, Ayisha Affo; Dotro, Gabriela; Cincinelli, Alessandra; Lyu, Tao (Elsevier, 2025)
The performance of treatment wetlands (TWs), as a nature-based solution, in mitigating persistent per- and polyfluoroalkyl substances (PFAS) and their interactions with existing treatment flowsheets remain unclear. This study investigated PFAS removal in two full-scale surface flow TWs treating secondary effluent from different domestic wastewater treatment plants (WWTPs). The systems demonstrated their capacities to safeguard natural water bodies by achieving discharge levels of the legacy PFOS (4–4.6 ng L−1) and PFOA (1.79–3.27 ng L−1) with removal efficiencies of 29%–38% and 15%–34%, respectively. Further upstream and downstream water quality monitoring in receiving waters is required to accurately evaluate PFAS contributions from WWTP effluents. Partitioning behaviour analysis revealed that sediment adsorption was the dominant removal pathway, achieving removal rates 16–61 times higher than plant uptake for PFOS and 1.8–6 times higher for PFOA. Sediment iron content, depth, and bulk density were positively correlated with PFAS sequestration, highlighting their importance in controlling PFAS mobility. PFOS accumulation in the sediment was greater in the TW for the WWTP dosing with ferric sulphate than the WWTP without chemical dosing (2.80 mg m−2 y−1 vs. 1.34 mg m−2 y−1). Notably, a conventional mass balance analysis was challenged by the transformation of PFAS precursors into terminal compounds, including PFOS and PFOA, potentially inflating input concentrations and contributing to mass imbalance during treatment. Further research is necessary to address these complexities, but the findings are encouraging for the use of TWs as scalable, eco-friendly solutions for mitigating PFAS pollution and are instructive for optimising wetland design and operation to safeguard aquatic ecosystems.
Keywords: Emerging micropollutant; Free water surface (FWS) wetland; Green infrastructure; Integrated constructed wetland (ICW); Nature-based solution; Upstream chemical dosing; 4004 Chemical Engineering; 40 Engineering; 4011 Environmental Engineering; 15 Life on Land; 4005 Civil engineering